2018
DOI: 10.1029/2018jb015653
|View full text |Cite
|
Sign up to set email alerts
|

Upscaled Anisotropic Methane Hydrate Critical State Model for Turbidite Hydrate‐Bearing Sediments at East Nankai Trough

Abstract: Turbidite formation is a common feature of natural hydrate‐bearing sediments that has been observed and reported at several hydrate exploration sites. It is therefore important to incorporate this anisotropic geological feature into the constitutive modeling when evaluating the geomechanical risks involved during hydrate‐based gas production. To date, a number of constitutive models have been proposed to capture the isotropic geomechanical behavior of homogeneous hydrate‐bearing sediments. Since the turbidite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…A third nonlaboratory study relevant for sediment behavior in hydrate reservoirs is focused on the development of a realistic critical state model for turbiditic sediments in the Nankai Trough, where the Japan Oil, Gas and Metals National Corporation conducted the first deep water gas hydrate production test in 2013 (Yamamoto et al, ). Instead of directly measuring sediment physical properties, Zhou et al () use borehole logs and the results of laboratory geomechanical analyses that constrain these properties in order to calibrate a sophisticated anisotropic model. They report that application of this new model within a thermal‐hydraulic‐mechanical (THM) reservoir simulator more closely reproduces the production pattern for water and gas from the 2013 test than does an older, isotropic critical state model.…”
Section: Special Section Themesmentioning
confidence: 99%
See 3 more Smart Citations
“…A third nonlaboratory study relevant for sediment behavior in hydrate reservoirs is focused on the development of a realistic critical state model for turbiditic sediments in the Nankai Trough, where the Japan Oil, Gas and Metals National Corporation conducted the first deep water gas hydrate production test in 2013 (Yamamoto et al, ). Instead of directly measuring sediment physical properties, Zhou et al () use borehole logs and the results of laboratory geomechanical analyses that constrain these properties in order to calibrate a sophisticated anisotropic model. They report that application of this new model within a thermal‐hydraulic‐mechanical (THM) reservoir simulator more closely reproduces the production pattern for water and gas from the 2013 test than does an older, isotropic critical state model.…”
Section: Special Section Themesmentioning
confidence: 99%
“…A third nonlaboratory study relevant for sediment behavior in hydrate reservoirs is focused on the development of a realistic critical state model for turbiditic sediments in the Nankai Trough, where the Japan Oil, Gas and Metals National Corporation conducted the first deep water gas hydrate production test in 2013 (Yamamoto et al, 2014). Instead of directly measuring sediment physical properties, Zhou et al (2018) 10.1029/2019JB018186…”
Section: Geomechanical and Hydraulic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Uneven distribution of hydrate will cause the heterogeneity of the sample, lowering its representativeness. Zhou et al [23] proposed an advanced soil model to better represent the heterogeneous structure of the hydrate-bearing sediments, and gave more accurate mechanical responses for numerical simulation. Liu et al [24] modeled specimens with uneven hydrate distributions, simulated the triaxial compression test process of the specimens using the discrete element method, and confirmed that the heterogeneity of hydrate distribution has great impacts on the mechanical properties of HBS.…”
Section: Introductionmentioning
confidence: 99%